El padre Saturnino con tres Yaguas - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó al padre Saturino en compañia de un grupo de indigenas Yaguas.
ENGLISH: Father Saturino was observed in the company of a group of Yagua indigenous people.

SPANISH: Se observó al padre Saturino en compañia de un grupo de indigenas Yaguas.
ENGLISH: Father Saturino was observed in the company of a group of Yagua indigenous people.
Father Saturnino with three Yaguas
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Religion|~|Evangelization|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Religion|~|Evangelización|~|Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Religion|~|Evangelization